2019
DOI: 10.1128/aac.01193-19
|View full text |Cite
|
Sign up to set email alerts
|

HAMLET, a Protein Complex from Human Milk, Has Bactericidal Activity and Enhances the Activity of Antibiotics against Pathogenic Streptococci

Abstract: HAMLET (human alpha-lactalbumin made lethal to tumor cells) is a protein-lipid complex derived from human milk that was first described for its tumoricidal activity. Later studies showed that HAMLET also has direct bactericidal activity against select species of bacteria, with highest activity against Streptococcus pneumoniae. Additionally, HAMLET in combination with various antimicrobial agents can make a broad range of antibiotic-resistant bacterial species sensitive to antibiotics. Here, we show that HAMLET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
0
18
0
2
Order By: Relevance
“…HAMLET as a treatment strategy is unique in that it has no cytotoxic effect on normal, healthy cells, but possesses a broad bactericidal and tumoricidal activity [2,6]. Since its discovery, antibacterial effects against several respiratory pathogens, including S. pneumoniae, Streptococcus pyogenes, Mycobacterium tuberculosis and Haemophilus influenzae have been described [1,4,5]. Additionally, anti-tumor activity against more than 40 different tumor types have been determined and HAMLET is currently in Phase I/II trial for treatment of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAMLET as a treatment strategy is unique in that it has no cytotoxic effect on normal, healthy cells, but possesses a broad bactericidal and tumoricidal activity [2,6]. Since its discovery, antibacterial effects against several respiratory pathogens, including S. pneumoniae, Streptococcus pyogenes, Mycobacterium tuberculosis and Haemophilus influenzae have been described [1,4,5]. Additionally, anti-tumor activity against more than 40 different tumor types have been determined and HAMLET is currently in Phase I/II trial for treatment of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HAMLET (Human Alpha‐lactalbumin Made LEthal to Tumor cells) is a complex consisting of the human milk protein alpha‐lactalbumin (αLA) in a partially unfolded state and oleic acid, that exhibit both selective bactericidal activity [1] and broad and potent tumoricidal effects [2, 3]. As of today, HAMLET has shown a direct bactericidal activity against numerous respiratory pathogens [1, 4, 5] as well as efficacy against 40 different cancer cell‐lines and primary tumors of different origin, without exerting cytotoxic effects against healthy, differentiated cells, in vitro or in vivo [2, 610]. Even though HAMLET spares healthy cells, it can still bind to and induce an increased level of intracellular calcium in these cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that HM has natural antimicrobial properties against several pathogenic microorganisms including Staphylococcus aureus (Ackerman et al, 2018; Reis et al, 2016; Schlievert et al, 2019; Zhang et al, 2017), Escherichia coli (Jiang et al, 2016; Reis et al, 2016; Schlievert et al, 2019), Candida (Gunyakti & Asan-Ozusaglam, 2019), Shigella (Sharma et al, 2017), Klebsiella pneumoniae (Lorico & Pérez, 2012), Streptococcus (Ackerman et al, 2017, 2018; Alamiri et al, 2019; Lin et al, 2017), and Pseudomonas aeruginosa (Takci et al, 2012). Although the contamination of HM with C. sakazakii has been previously reported (Bowen et al, 2017; McMullan et al, 2018; Sundararajan et al, 2018), to the best of the authors’ knowledge this is the first study to specifically evaluate the AC against this microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Other antimicrobial proteins may enhance the effectiveness of antibiotics against AMR pathogens. For example, the human milk factor HAMLET (human α-lactalbumin made lethal to tumor cells) has been shown to directly target as well as enhance the effectiveness of antibiotics against drug-resistant Staphylococcus aureus and pathogenic streptococci [79,80], which could reduce the duration of antibiotic therapy needed to treat an infection and thereby minimize associated harms to infants' developing microbiomes [4]. Recent experimental studies suggest that other antimicrobial peptides present in human milk, such as β-defensins, may also be able to work in synergy with antibiotics to lower the minimum inhibitory concentrations of intracellular pathogens [81].…”
Section: Antimicrobial Factorsmentioning
confidence: 99%